PERAN BANK INDONESIA DALAM PENANGGULANGAN TINDAK PIDANA PERBANKAN - Budiyono Budiyono (Jurnal Dinamika Hukum, 2011)
Management activity in banking area Indonesia have strategic role to support national development execution. Referring to the mentioned, hence in face of national economy growth which is complex progressively and also financial system which progressively go forward, to be needed by adjustment of policy in economic area is including banking sector, adjustment needed in line with international banking norm growth. Law which have been invited in the Act No. 7, 1992 as have been altered and added with Act No. 10, 1998 about Banking, related to problem of doing an injustice to banking, this law is expected can close over lacking of found on previous law. Keyword :  banking crime, role, white collar crime